Efficacy of Short Course of Preksha Dhyana for Functional Abdominal Pain Disorder in a Busy Pediatric Clinic - Mehta, Vijay; Mehta, Akshay; Patel, Samit; Irastorza, Laura; Rizvi, Syed Ahsan; Abomoelak, Bassam; Mehta, Naina; Mehta, Devendra (Frontiers in Pediatrics, 2021)
Introduction: Mind Body Techniques such as meditation improve symptoms in children and adults with IBS. Typical courses, however, are lengthy and difficult to administer. We report our experience with a cost-effective short course of Preksha Dhyana (PD), a child friendly focused meditation with yoga. Method: Physicians deliver focused meditation while medical assistants taught yoga. Three sessions were administered biweekly with recommendations for daily practice. Pain severity Likert scores were compared with a treatment as usual (TAU) historical control. Anxiety scores were compared from baseline in PD group. Results: Thirty PD patients aged 9-17 (20 female) and 52 consecutive TAU group aged 5-17 (33 female) were reviewed. The biweekly sessions had high (71%) completion rates. Utilization rates of PD were similar to TAU despite added sessions. PD group had an average time of follow up of 8.9 +/- 9.4 vs 6.0 +/-3.9 months in the TAU group (p=0.522). Changes in pain scores from baseline showed improvement in the PD group 0.67 +/-0.13 vs TAU 1.39 +/-0.11 (p=0.0003). In the PD group, anxiety scores improved significantly from baseline (0.5 vs 1, P<0.001). Pain improved in 93% (28/30) and resolved in 47% (14/30). Conclusion: Short course of PM was successfully embedded in a busy pediatric office without additional staffing. The approach proved cost effective without increasing overall healthcare utilization and showed significant benefits over TAU. Pending RCT confirmation, this offers a cost-effective method to incorporate mind body techniques into a pediatric office practice.